Web-Based Thesis Management Information System Design - Nugraha, Yopi (Politeknik Ganesha Medan, 2022)
One of the academic activities that still uses manuals is the submission of a final assignment or thesis. Submission of the final assignment at starts from submitting a title which is filled out through a form then submitted to the head of the study program for review and approval. After the verification is complete, students can immediately take part in pre-Thesis Proposal Seminar provisional guidance and when finished, they can immediately take part in the proposal seminar as well as the assembly. the system that runs at arrowroot in presenting information on student final assignments it is still manual, namely using bookkeeping/paper, submission of data which makes the provision of information quite long and the data is easily scattered until it is lost. It can be observed from the opportunities and business where there is a management system that allows researchers to implement a system with the concept of an online thesis management system with a website-based application so that student final assignment data can be properly managed and accessed through internet media and in building this system researchers use the Software Development Life Cycle (SDLC) with the waterfall approach method, namely analysis, design, implementation and testing. By using this method, it can increase the efficiency of the average time than before. As well as saving costs for other needs in making thesis report data and facilitating the management of final project information data.